Comparison of Field Data Processing Methods for the Evaluation of Topographic Effects. Issue 4 (November 2016) - Wood, Clinton M.; Cox, Brady R.
This paper presents a comparison of field data processing methods used to evaluate topographic effects. A data set of 52 weak motion events recorded using a dense array of seismometers located on steep, complex topography is analyzed. Both time domain and frequency domain analysis methods are evaluated for effectiveness at resolving the amplitude and frequency range associated with topographic effects. Results from this study indicate the median reference method (MRM) provides a more stable estimate of the frequency range and expected amplification value than the standard spectral ratio (SSR) or horizontal-to-vertical spectral ratio (HVSR) methods.